Experimental Study of Polymer Injection on Oil Recovery Factor Enhancement Using Homogenous and Heterogenous Micromodel Porous Media - Boni Swadesi; Roiduz Zumar; Sinosa Husenido; Dedy Kristanto; Indah Widiyaningsih; Sri Murni (Universitas Islam Riau (UIR) Press, 2022)
Polymer injection is one method of chemical enhanced oil recovery, which increase oil recovery by improving mobility when viscous fingering occurred in waterflooding operation. The result of polymer injection is better sweep efficiency, which is presented by more even distribution of the injected fluid. However, in common laboratory evaluation for polymer injection testing, it was no visual observation that presents directly for the fluiddistribution. This experimental study was carried out to visually observe the polymer injection mechanism to displace oil by micromodel as porous media. The micromodel used in this study is transparent acrylic material which was etched by laser engraving technology to create grains that resemble reservoir rocks. The micromodel was saturated by brine water and light oil respectively as initial reservoir fluids. Then, the water was injected as waterflooding operation to displace oil in a micromodel. Hydrolyzed Polyacrylamide (HPAM) polymer with various concentrations were injected into the micromodel as the last scenario. Through this experiment, the movement and distribution of fluids in chemical enhanced oil recovery especiallypolymer injection was able to be recorded for further analysis. Observation for each scenario was done by Digital Image Analysis (DIA). The micromodel flooding results showed that the higher concentration of polymer would give higher oil recovery. The front stability and good distribution of polymer will result in better sweep efficiency, then higher oil recovery will be achieved. This experiment gives result visually how polymer enhance oil recovery. This experiment is expected to be leading innovation for Enhanced Oil Recovery (EOR) laboratory studies in Indonesia